2020
DOI: 10.1016/j.jep.2020.113163
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Artemisia campestris subsp. glutinosa (Besser) Batt. inhibits HIV–1 replication in vitro through the activity of terpenes and flavonoids on viral entry and NF–κB pathway

Abstract: Ethno–pharmacological relevance The genus Artemisia spp. is well known for its anti–infectious properties and its high content in anti–infectious compounds, like the well–known sweet wormwood ( Artemisia annua L.). Another Artemisia species, Artemisia campestris subsp. glutinosa (Besser) Batt., field wormwood, has been traditionally used as medicinal plant in the Mediterranean region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…XAN is identified as an active compound in herbs/plants with a long application in traditional medicine, such as Baccharis pentlandii D.C. [ 15 ], Dracocephalum kotschyi Boiss [ 16 , 17 , 18 , 19 ], Ocimum gratissimum L. [ 20 ], Baccharis densiflora Wedd [ 21 ], and Artemisia campestris L. [ 22 ]. Several studies reported the antioxidant [ 7 ], anticancer [ 7 , 17 , 18 , 19 , 21 , 23 ], antimicrobial [ 7 , 22 ], and anti-inflammatory [ 7 ] properties of XAN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XAN is identified as an active compound in herbs/plants with a long application in traditional medicine, such as Baccharis pentlandii D.C. [ 15 ], Dracocephalum kotschyi Boiss [ 16 , 17 , 18 , 19 ], Ocimum gratissimum L. [ 20 ], Baccharis densiflora Wedd [ 21 ], and Artemisia campestris L. [ 22 ]. Several studies reported the antioxidant [ 7 ], anticancer [ 7 , 17 , 18 , 19 , 21 , 23 ], antimicrobial [ 7 , 22 ], and anti-inflammatory [ 7 ] properties of XAN.…”
Section: Introductionmentioning
confidence: 99%
“…XAN is identified as an active compound in herbs/plants with a long application in traditional medicine, such as Baccharis pentlandii D.C. [ 15 ], Dracocephalum kotschyi Boiss [ 16 , 17 , 18 , 19 ], Ocimum gratissimum L. [ 20 ], Baccharis densiflora Wedd [ 21 ], and Artemisia campestris L. [ 22 ]. Several studies reported the antioxidant [ 7 ], anticancer [ 7 , 17 , 18 , 19 , 21 , 23 ], antimicrobial [ 7 , 22 ], and anti-inflammatory [ 7 ] properties of XAN. The antitumoral activity of XAN has been related to its ability to inhibit cancer cell viability/proliferation [ 7 , 17 , 18 , 21 , 23 ], angiogenesis [ 16 ], cancer-related enzymes [ 19 ], and to induce apoptosis [ 17 , 23 ] and cell cycle arrest [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond anti-parasite activity, artemisinin and its derivatives exhibit the therapeutic potentials for viral infections, inflammatory disease, autoimmune diseases and cancer [44][45][46][47]. Also, the extracts of Artemisia annua, particularly artemisinin and flavonoids, have been reported to have numerous pharmacological properties [48,49]. However, we still know little about the action mode of Artemisinin and the relevant components.…”
Section: Discussionmentioning
confidence: 99%
“…subsp. glutinosa exhibit in vitro inhibitory activity against HIV, with the ethanolic extract demonstrating greater potency (15). Bio-guided fractionation of the ethanolic extract resulted in the identification of two terpenes: canrenone and damsin, and four flavonoids: acerosin, xanthomicrol, cardamonin, and 6, 2′, 4′-trimethoxyflavone.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Artemisia campestris, commonly called field wormwood, underwent pharmacological reassessment (14). Traditionally utilized as an antiseptic (15), A. campestris found application in treating pleurisy, a condition arising from viral or bacterial infections (16). Additionally, indigenous North American communities employ extracts of A. campestris to alleviate common colds induced by coronavirus or rhinovirus, although the underlying mechanism and active compounds remain undisclosed (17).…”
Section: Introductionmentioning
confidence: 99%